Peran Orang Tua Dalam Stimulasi Perkembangan Bahasa Anak Usia 3–5 Tahun - Anidi Anidi; Fernandes Arung; Chairan Zibar L. Parisu; Arna Juwairiyah (FKIP UNSULTRA, 2025)
Language development is one of the important aspects in the growth and development of early childhood, especially in the age range of 3-5 years which is a critical period in the formation of communication skills. Parents, as the first and main educators for children, have a strategic role in providing appropriate stimulation to support children's language development. This literature study aims to explore various scientific findings that discuss parental involvement in stimulating children's language through daily interactions, reading habits together, educational games, and the use of appropriate digital media. The method used in this study is a literature review from various relevant national and international journals in the period 2018 to 2024. The results of the study show that active parental involvement, either through two-way communication, play activities, or the habit of reading stories, greatly influences children's vocabulary, syntax, and speaking skills. On the other hand, lack of stimulation or passive communication patterns can significantly inhibit language development. Therefore, it is important for parents to get education about effective language stimulation strategies according to the child's developmental stage. This study recommends the importance of collaboration between parents, educators, and child health workers in creating a conducive linguistic environment for early childhood.